Peningkatan Ketrampilan dan Pembelajaran Kearifan Lokal Dalam Pembuatan Minuman Kopi Di Desa Wisata Kemiren, Kabupaten Banyuwangi, Jawa Timur - Basalamah, Anwar; Ayuningsih, Sri Fajar; Abdillah, Fitri; Susanto, Sandi; Rachmat, Timotius Agus; Prihandrijanti, Maria (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Coffee is a beverage that is a drink of friendship for the Osing people in Banyuwangi. Coffee is also the main drink in the development of the Kemiren tourism destination. The aim of PkM is to increase the ability of local communities in serving and marketing coffee through social media. The implementation of this activity is focused on the needs of the Kemiren tourism village partners. The form of activity is a training and coaching clinic consisting of training on serving coffee drinks, developing a coffee menu and training on product styling & photography. The location was centered at Jaran Goyang Cafe, Kemiren Village, Banyuwangi with the number of participants reaching 25 people. The PkM results show the enthusiasm of the community following the program and discussing the development of Osing Coffee. Several trainings that have been carried out show differences in the closeness of interactions which influence the enthusiasm to improve the quality of coffee serving. Evaluation is carried out by holding a small competition among participants and assessed by the PkM team. These indicators are expected to strengthen the program's impact in increasing the community's skills and enthusiasm to develop Osing Coffee as part of a local tourism attraction. Suggestions for the next PKM activity are to provide the required training materials in the form of basic barista skills and optimize social media as a means of promotion and marketing